Selection bias in ecological studies. (December 2017) - Rousson, V.; Rosselet, P.C.; Paccaud, F.
Highlights: Despite various limitations, ecological studies merit interest in public health. Selection bias is an important under-recognized problem in ecological studies. A random selection from a well-defined population of countries should be warranted.